Implementation of Anyflip-based online IPS E-module in Elementary Schools - Eldyana Citra Laksita; Tiominar Febrianti Puspita Sari; Wilda Nur Laila; Nurdiansyah (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
The progress of the times is increasingly integrating technology to improve learning in schools. By implementing Anyflip-based E-modules, an application can enable the creation of digital learning materials in an interactive format, especially in social studies learning in elementary schools. With this research, the author uses a qualitative approach with the method of literature study or literature research through sources. This research is prepared based on the principle of in-depth and detailed literature review but made simple so that readers can easily understand the essence of the application of online Anyflip-based social studies E-modules in elementary schools. The application of E-modules has great potential in implementing effective learning in primary schools.